Особливості японської моди - Нарумі Хіросі (Народна творчість та етнографія, 2009)
In the article basic directions of the modern Japanese culture of clothes are analyzed: history of Europeanization of fashion, basic directions and fashionable brands, authors’ styles of the Japanese designers. The spheres of the use of national clothes of kimono and yofuku (“the clothes in the western style") are differentiated.